2017
DOI: 10.1159/000477498
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-Up of Choroidal Neovascularization due to Angioid Streaks with pro re nata Intravitreal Anti-VEGF Treatment

Abstract: Purpose: To evaluate the long-term outcomes of intravitreal anti-vascular endothelial growth factor (VEGF) drugs with a pro re nata (PRN) regimen for the treatment of choroidal neovascularization (CNV) secondary to angioid streaks (AS). Methods: This is a retrospective, multicenter, noncomparative case series of consecutive AS eyes affected by treatment-naïve CNV. A complete ophthalmologic examination was performed every 30-45 days after the loading phase, including fluorescein angiography and/or optical coher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…In this study, patients had a mean age of 53.2 ± 12.1 years at the time of CNV diagnosis/treatment initiation, which is consistent with previous studies [ 12 , 16 , 17 ]. Moreover, the mean age of patients with PXE and angioid streaks complicated with CNV seems to be significantly lower than in patients with no PXE, 49.0 ± 10.5 years vs. 58.1 ± 12.4, P =0.023.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In this study, patients had a mean age of 53.2 ± 12.1 years at the time of CNV diagnosis/treatment initiation, which is consistent with previous studies [ 12 , 16 , 17 ]. Moreover, the mean age of patients with PXE and angioid streaks complicated with CNV seems to be significantly lower than in patients with no PXE, 49.0 ± 10.5 years vs. 58.1 ± 12.4, P =0.023.…”
Section: Discussionsupporting
confidence: 90%
“…However, not all studies are consensual regarding the improvement of BCVA and its stability over time after anti-VEGF treatment. For instance, Giacomelli et al observed a progressive deterioration in BCVA after treatment with ranibizumab or bevacizumab in PRN protocol [ 16 ]. Iacono et al investigated the effects of intravitreal bevacizumab in 15 patients with non-subfoveal CNV secondary to angioid streaks and observed a statistically significant BCVA worsening at 3 years (65.8 ± 15.0 letters) compared with BCVA at 1 year (80.1 ± 5.4 letters) [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, attention has been focused on the function of VEGF in light of its role as a therapeutic target 34 . VEGF is a key regulator of angiogenesis, and withdrawal or interference with its function leads to cessation of vascular growth and neovascular regression 35 . VEGF expression has been shown in experimental choroidal neovascularisation, and shown to induce choroidal neovascularisation growth in animals.…”
Section: Discussionmentioning
confidence: 99%
“…10 Many studies have confirmed the efficacy of intravitreal anti-VEGF therapy on CNV secondary to ASs. [13][14][15][16][17][18][19][20]27 Intravitreal injections have improved the functional outcome of these patients by controlling CNV activity. The French PIXEL study has shown that the mean VA was maintained at one year with treatment with 0.5 mg of ranibizumab and it remained stable for up to four years.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it varies from one study to another. [15][16][17][18][19][20] Macular atrophy of the retinal pigment epithelium (RPE) has been proposed as one of the possible causes of the long-term visual loss, but its progression rate has never been reported. 20,21 The aims of this study were to assess the very long-term prognosis of eyes with CNV secondary to ASs due to PXE in the anti-VEGF era and to investigate central RPE atrophy enlargement in AS eyes with or without PXE.…”
mentioning
confidence: 99%